Pengaruh Pelayanan Reproduksi Terpadu terhadap Skrining Kanker Payudara pada Akseptor KB Hormonal - Kadek Novi Marlinawati; Syajaratuddur Faiqah; Rita Sopiatun; Baiq Yuni Fitri Hamidiyanti (Indonesian Journal Publisher, 2024)
Latar Belakang: Pada tahun 2022, jumlah kasus baru kanker payudara mencapai 66.271 kasus (16,2%), data SADANIS di Kabupaten Lombok Barat tahun 2023 sebanyak 11.245 WUS dan curiga kanker sebanyak 14 kasus. Etiologi penyakit kanker payudara berhubungan dengan keadaan hormonal, salah satunya terdapat pada alat kontrasepsi hormonal sehingga diperlukan suatu inovasi pelayanan yaitu Pelayanan Kesehatan Reproduksi Terpadu Pelayanan Keluarga Berencana.Tujuan: mengetahui Pengaruh Pelayanan Kesehatan Reproduksi Terpadu pada Akseptor KB Hormonal terhadap Skrining Kanker Payudara di wilayah kerja Puskesmas Labuapi. Metode: Penelitian ini menggunakan rancangan penelitian yaitu Quasi Experimental dengan desain Non-Equivalent Control Group Design. Sampel yang diambil sebanyak 44 sampel, dibagi menjadi 2 kelompok kasus dan kontrol. Teknik pengambilan sampel menggunakan purposive sampling. Uji analisis yang digunakan yaitu Chi Square. Hasil: analisa post test dengan uji statistik Chi Square, pada pengetauan diperoleh nilai signifikansi 0,038, analisa sikap diperoleh nilai signifikansi 0,022, analisis kesediaan diperoleh nilai signifikansi 0,038. Hasil analisis ketiga kategori diperoleh nilai signifikansi < 0,05 sehingga ada pengaruh Pelayanan Kesehatan Reproduksi Terpadu Pada Akseptor KB Hormonal terhadap Pengetahuan, Sikap, dan Kesediaan Skrining Kanker Payudara. Kesimpulan: terdapat Pengaruh Pelayanan Kesehatan Reproduksi Terpadu pada Akseptor KB Hormonal terhadap skrining kanker payudara ABSTRACT Background: In 2022, the number of new cases of breast cancer reached 66,271 cases (16.2%), SADANIS data in West Lombok Regency in 2023 is 11,245 WUS and suspected of cancer as many as 14 cases. The etiology of breast cancer is related to hormonal conditions, one of which is found in hormonal contraceptives. The problem solving is an integrated service innovation namely Reproductive Health Services combined with Family Planning Services. Purpose: To determine the effect of integrated reproductive health services on hormonal contraceptive acceptors on breast cancer screening in the Labuapi health center working area. Methods: The research design used Quasi Experimental with a Non-Equivalent Control Group Design. The samples were 44 hormonal birth control acceptors who were divided into 2 groups, case and control. The sampling technique uses purposive sampling and the analytics uses non parametrik Chi Squre. Results: the post test results, in the knowledge obtained a significance value of 0.038, the attitude obtained a significance value of 0.022, and the willingness obtained a significance value of 0.038. The three categories obtained a significance value of < 0.05 so conclude there was an effect of Integrated Reproductive Health Services on Hormonal Birth Control Acceptors on knowledge, attitudes and willingness to carry out breast cancer screening. Conclusion: There is an influence of Integrated Reproductive Health Services on Hormonal Birth Control Acceptors on breast cancer screening Background: In 2022, the number of new cases of breast cancer reached 66,271 cases (16.2%), SADANIS data in West Lombok Regency in 2023 is 11,245 WUS and suspected of cancer as many as 14 cases. The etiology of breast cancer is related to hormonal conditions, one of which is found in hormonal contraceptives. The problem solving is an integrated service innovation namely Reproductive Health Services combined with Family Planning Services. Purpose: To determine the effect of integrated reproductive health services on hormonal contraceptive acceptors on breast cancer screening in the Labuapi health center working area. Methods: The research design used Quasi Experimental with a Non-Equivalent Control Group Design. The samples were 44 hormonal birth control acceptors who were divided into 2 groups, case and control. The sampling technique uses purposive sampling and the analytics uses non parametrik Chi Squre. Results: the post test results, in the knowledge obtained a significance value of 0.038, the attitude obtained a significance value of 0.022, and the willingness obtained a significance value of 0.038. The three categories obtained a significance value of < 0.05 so conclude there was an effect of Integrated Reproductive Health Services on Hormonal Birth Control Acceptors on knowledge, attitudes and willingness to carry out breast cancer screening. Conclusion: There is an influence of Integrated Reproductive Health Services on Hormonal Birth Control Acceptors on breast cancer screening